Activation of immediate-early response gene c-Fos protein in the rat paralimbic cortices after myocardial infarction - Ahn, Ji Yun (Neural Regen Res, 2015)
c-Fos is a good biological marker for detecting the pathogenesis of central nervous system disorders. Few studies are reported on the change in myocardial infarction-induced c-Fos expression in the paralimbic regions. Thus, in this study, we investigated the changes in c-Fos expression in the rat cingulate and piriform cortices after myocardial infarction. Neuronal degeneration in cingulate and piriform cortices after myocardial infarction was detected using cresyl violet staining, NeuN immunohistochemistry and Fluoro-Jade B histofluorescence staining. c-Fos-immunoreactive cells were observed in cingulate and piriform cortices at 3 days after myocardial infarction and peaked at 7 and 14 days after myocardial infarction. But they were hardly observed at 56 days after myocardial infarction. The chronological change of c-Fos expression determined by western blot analysis was basically the same as that of c-Fos immunoreactivity. These results indicate that myocardial infarction can cause the chronological change of immediate-early response gene c-Fos protein expression, which might be associated with the neural activity induced by myocardial infarction.